2018
DOI: 10.1007/s00417-018-4174-7
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of erythrocyte sedimentation rate and C-reactive protein in patients with active uveitis

Abstract: PurposeTo relate erythrocyte sedimentation rates (ESR) and C-reactive protein (CRP) values to different uveitis entisties.MethodsA retrospective study of patients with a first episode of active uveitis visiting the Erasmus University Medical Center, uveitis clinic, Rotterdam, the Netherlands, was performed. Levels of ESR and CRP were determined within 2 weeks and 1 week after onset of uveitis, respectively. Uveitis had to be of unknown origin at that moment. The specific etiologic groups were related to ESR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The most common investigations done were CBC, CXR, Mantoux test (77.6%), and ESR. CBC, ESR and C-reactive protein (CRP) were found to be within the normal limit in the majority of uveitis patients and were not related to any specific cause of uveitis in an earlier study [9] . CXR was abnormal in only 15% of active uveitis cases in a cross-control study reported by Groen et al [10] .…”
Section: Discussionmentioning
confidence: 80%
“…The most common investigations done were CBC, CXR, Mantoux test (77.6%), and ESR. CBC, ESR and C-reactive protein (CRP) were found to be within the normal limit in the majority of uveitis patients and were not related to any specific cause of uveitis in an earlier study [9] . CXR was abnormal in only 15% of active uveitis cases in a cross-control study reported by Groen et al [10] .…”
Section: Discussionmentioning
confidence: 80%
“…CRP can have various values in sinusitis, and increased values can aid in its early diagnosis [ 996 , 997 ]. Moreover, CRP concentrations can vary from relatively normal to notably elevated values in uveitis cases [ 998 ]. An old study has shown various serum CRP levels in acute otitis media cases, but high values (>20 mg/L) were observed in those with bacterial infection [ 999 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…The proteins S100A8 [myeloid-related protein 8) and S100A9 [myeloid-related protein 14) combine to make calprotectin, which is primarily produced by activated granulocytes and monocytes in the blood and in amed tissues [5]. As it binds toll-like receptor 4 (TLR4)-like damage-associated molecular patterns (DAMPs), it is regarded as an endogenous activator of innate immune response, boosting the release of proin ammatory cytokines, [6].…”
Section: Introductionmentioning
confidence: 99%